The Role of Affects and Emotional Styles in the Relationship Between Parents and Preschool Children - Carolina Facci; Andrea Baroncelli; Enrica Ciucci (Children)
Background/Objectives: Parent–child relationships represent a key factor for the quality of developmental trajectories and impact on children’s social and emotional competence. Therefore, research has advanced the role of parenting by showing the significance of differentiating between distinctive aspects of a parent’s behaviors. This study aims to investigate the role of the feelings experienced in parent–child relationships (e.g., warmth and negative feelings), considering the moderating role of the parental styles toward children’s emotions (e.g., coaching and dismissing). Methods: A total of 136 mothers (M = 38.09 years, SD = 4.51 anni, 48.5% high school degree) with a preschool child (age range 3–5 years) in Central Italy have been involved in a survey during the pandemic period. Results: Multiple regression analyses show that warmth and negative feelings are associated with positive parenting; however, the moderation effect of the dismissing style on both warmth and negative feelings emerged. Conclusions: Despite the characteristics of the data collection period, the results suggest the importance of considering the emotion-related dimensions between parents and their children as they seem to influence parenting behaviors.